Validity and Reliability of the Chronic Respiratory Disease Questionnaire in Elderly Individuals with Mild to Moderate Non-Cystic Fibrosis Bronchiectasis - Vodanovich, D.; Bicknell, T.; Holland, A.; Hill, C.; Cecins, N.; Jenkins, Susan; McDonald, C.; Burge, A.; Thompson, P.; Stirling, R.; Lee, A. (S. Karger AG, 2015)
Background: The chronic respiratory disease questionnaire (CRDQ) is designed to assess health-related quality of life (HRQOL) in chronic respiratory conditions, but its reliability, validity and responsiveness in individuals with mild to moderate non-cystic fibrosis (CF) bronchiectasis are unclear. Objectives: This study aimed to determine measurement properties of the CRDQ in non-CF bronchiectasis. Methods: Participants with non-CF bronchiectasis involved in a randomised controlled trial of exercise training were recruited. Internal consistency was assessed using Cronbach's a. Over 8 weeks, reliability was evaluated using intra-class correlation coefficients and Bland-Altman analysis for measures of agreement. Convergent and divergent validity was assessed by correlations with the other HRQOL questionnaires and the Hospital Anxiety and Depression Scale (HADS). The responsiveness to exercise training was assessed using effect sizes and standardised response means. Results: Eighty-five participants were included (mean age ± SD, 64 ± 13 years). Internal consistency was adequate (>0.7) for all CRDQ domains and the total score. Test-retest reliability ranged from 0.69 to 0.85 for each CRDQ domain and was 0.82 for the total score. Dyspnoea (CRDQ) was related to St George's respiratory questionnaire (SGRQ) symptoms only (r = 0.38), with no relationship to the Leicester cough questionnaire (LCQ) or HADS. Moderate correlations were found between the total score of the CRDQ, the SGRQ (rs = -0.49) and the LCQ score (rs = 0.51). Lower CRDQ scores were associated with higher anxiety and depression (rs = -0.46 to -0.56). The responsiveness of the CRDQ was small (effect size 0.1-0.24). Conclusions: The CRDQ is a valid and reliable measure of HRQOL in mild to moderate non-CF bronchiectasis, but responsiveness was limited. © 2015 S. Karger AG, Basel